Perancangan Arsitektur Teknologi Informasi Menggunakan Framework TOGAF Pada Koperasi Budi Karya - Arvini Anindhita; Royana Afwani; Ida Bagus Ketut Widiartha (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
This study discusses the design of information technology enterprise architecture in the cooperation of Budi Karya. The main problem encountered is that the management still uses a bookkeeping system. The information obtained in each section has not been integrated with other, the IT management organization structure is not sufficient because there is no staff who have specialized IT experts, and require development in information technology. This was stated in one of the Budi Karya cooperation missions which read